Heterozygous COL4A3 Variants in Histologically Diagnosed Focal Segmental Glomerulosclerosis - Braunisch, Matthias C.; Büttner-Herold, Maike; Günthner, Roman; Satanovskij, Robin; Riedhammer, Korbinian M.; Herr, Pierre-Maurice; Klein, Hanns-Georg; Wahl, Dagmar; Küchle, Claudius; Renders, Lutz; Heemann, Uwe; Schmaderer, Christoph; et al. (Frontiers in Pediatrics, 2018)
Introduction: Steroid-resistant nephrotic syndrome (SRNS) is one of the most frequent causes for chronic kidney disease in childhood. In approximately 30% of these cases a genetic cause can be identified. The histological finding in SRNS is often focal segmental glomerulosclerosis (FSGS). In rare cases, however, pathogenic variants in genes associated with Alport syndrome can be identified in patients with the histological finding of FSGS. Materials and methods: Clinical information was collected out of clinical reports and medical history. Focused molecular genetic analysis included sequencing of COL4A5 and COL4A3 in the index patient. Segregation analysis of identified variants was performed in the parents and children of the index patient. Results: The female index patient developed mild proteinuria and microscopic hematuria in childhood (12 years of age). The histological examination of the kidney biopsies performed at the age of 21, 28, and 32 years showed findings partly compatible with FSGS. However, immunosuppressive treatment of the index patient did not lead to a sufficient reduction of in part nephrotic-range proteinuria. After the patient developed hearing impairment at the age of 34 years and her daughter was diagnosed with microscopic hematuria at the age of 6 years, re-examination of the index’s kidney biopsies by electron microscopy revealed textural changes of glomerular basement membrane compatible with Alport syndrome. Molecular genetic analysis identified two missense variants in COL4A3 in a compound heterozygous state with maternal and paternal inheritance. One of them is a novel variant that was also found in the 6 year old daughter of the index patient who presented with microscopic hematuria. Discussion: We were able to show that a novel variant combined with a previously described variant in compound heterozygous state resulted in a phenotype that was histologically associated with FSGS. Molecular genetic analysis therefore can be essential to solve difficult cases that show an unusual appearance and therefore improve diagnostic accuracy. Additionally, unnecessary and inefficient treatment with multiple side effects can be avoided.